Polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel and preparation method thereof

Through the design of polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel, the cross-linking of polyvinylimine with citric acid and freeze-thawing cycle of polyvinyl alcohol is solved, and the light stability and mechanical strength of traditional fluorescent hydrogels are insufficient. Problem, high mechanical strength and stable fluorescence characteristics are achieved, and are suitable for fields such as anti-counterfeiting.

CN119219944AActive Publication Date: 2024-12-31BAICHUAN (SHANDONG) NEW MATERIALS TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411371619.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Traditional fluorescent hydrogels have shortcomings in light stability and mechanical strength, and are difficult to meet the application needs of high-tech fields related to luminescents.

Method used

Polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel is used to form a first network through cross-linking of polyethyleneimine and citric acid, and a second network is formed by freeze-thawing cycle of polyvinyl alcohol, which significantly improves the mechanics of the hydrogel. Performance and fluorescence characteristics.

Benefits of technology

It significantly improves the mechanical strength and fluorescence stability of the hydrogel, provides excellent intrinsic photoluminescent properties, and has a wide application potential, especially in the field of anti-counterfeiting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219944A_ABST
    Figure CN119219944A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogel, and particularly relates to polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel and a preparation method thereof. The polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel is composed of a first network formed by cross-linking polyethyleneimine and citric acid and a second network formed by freeze-thaw cycle of polyvinyl alcohol. In the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel, a first network formed by crosslinking of polyethyleneimine and citric acid is stably and uniformly distributed in a second network formed by freeze-thaw cycle of polyvinyl alcohol, so that the mechanical properties of the hydrogel are remarkably improved, and stable fluorescence characteristics are provided. And the polyvinyl alcohol crystal domain is used as a strong bond, so that the mechanical strength of the hydrogel is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels, and in particular relates to a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Polymer hydrogels, which are formed by cross-linking hydrophilic polymers and have a three-dimensional network structure with water as the dispersion medium, have become the preferred materials in the fields of human health monitoring, tissue engineering, environmental protection, agriculture, electronic gel industry and food industry due to their flexible synthesis methods, adjustable composition and mechanical properties, unique biocompatibility and high-water tissue environment for cell and tissue growth. Artificial gels have been widely used in such traditional fields, but their application in high-tech fields related to luminophores is limited. Therefore, fluorescent hydrogels with fluorescent emitting groups are also one of the hot spots in hydrogel research in recent years, and have attracted widespread attention in the fields of information storage and security, environmental monitoring and protection, drug delivery and tissue engineering.

[0004] Loading fluorescent materials into the 3D network of hydrogels is a win-win strategy, as hydrogels can provide mechanical and chemical stability for the fluorescent components. The introduction of fluorescent components also improves the structure and properties of hydrogels to a certain extent. Traditionally, fluorescent hydrogels are prepared by coupling or doping hydrogel matrices with fluorescent units such as semiconductor quantum dots, metal ligand complexes, lanthanide ions, and organic dyes. Traditional fluorescent hydrogels have some inherent defects, such as easy photobleaching, poor photostability, and low mechanical strength.

[0005] Some polymers containing only amide, carbonyl or fatty amine can achieve non-traditional intrinsic luminescence phenomenon of fluorescence emission in the absence of traditional fluorescent groups, and can also show strong fluorescence. Although these special luminescent materials show excellent photostability, high luminescence efficiency, good water solubility, biosafety and degradability, they lack functional cross-linking molecules and are difficult to use in the preparation of hydrogels. Summary of the invention

[0006] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel and a preparation method thereof. In the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel, the first network formed by cross-linking polyethyleneimine and citric acid is stably and evenly distributed in the second network formed by the freeze-thaw cycle of polyvinyl alcohol, which significantly improves the mechanical properties of the hydrogel and provides stable fluorescent properties. And the polyvinyl alcohol crystal domain acts as a strong bond, which significantly improves the mechanical strength of the hydrogel.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0008] In a first aspect, the present invention provides a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel, which consists of a first network formed by cross-linking polyethyleneimine and citric acid and a second network formed by freeze-thaw cycles of polyvinyl alcohol.

[0009] Preferably, the mass ratio of citric acid to polyethyleneimine is 1:(0.5-5), and the ratio of the total mass of polyethyleneimine and citric acid to the mass of polyvinyl alcohol is 1:(0.2-19.8).

[0010] In a second aspect, the present invention provides a method for preparing the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel as described in the first aspect, comprising the following steps:

[0011] Citric acid and polyethyleneimine are added to a polyvinyl alcohol aqueous solution to obtain a mixed solution, and the mixed solution is subjected to a heating reaction and a freeze-thaw cycle to obtain a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel.

[0012] Preferably, the mass density of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 2 to 20 wt.%.

[0013] Preferably, the total mass concentration of polyethyleneimine and citric acid in the mixed solution is 1 to 20 wt.%.

[0014] Preferably, the heating reaction temperature is 80°C to 120°C, and the time is 5 to 100 hours.

[0015] Preferably, the freeze-thaw cycle is specifically placed in an environment of -25°C to 0°C for 1 to 24 hours and then placed in an environment of 0°C to 35°C for 1 to 4 hours, and repeated 1 to 5 times.

[0016] Preferably, the polyvinyl alcohol aqueous solution is obtained by heating and dissolving polyvinyl alcohol in water.

[0017] More preferably, the temperature for heating and dissolving is 90° C. to 100° C., and the time is 1 to 2 hours.

[0018] In a third aspect, the present invention provides an application of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel as described in the first aspect in the field of anti-counterfeiting.

[0019] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:

[0020] The first network formed by cross-linking polyethyleneimine and citric acid in the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel is stably and evenly distributed in the second network formed by the freeze-thaw cycle of polyvinyl alcohol, which significantly improves the mechanical properties of the hydrogel and provides stable fluorescence properties. And the polyvinyl alcohol crystal domain acts as a strong bond, which significantly improves the mechanical strength of the hydrogel.

[0021] After the raw materials are mixed, a simple heating reaction can form the first network, and a freeze-thaw cycle can form the second network. The polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel can be prepared quickly and easily.

[0022] By controlling the content of the two networks, the strength and toughness of the hydrogel can be adjusted separately.

[0023] Polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel has excellent intrinsic photoluminescence properties and is expected to have great application potential in fields such as anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0025] Figure 1 The absorption spectrum and excitation spectrum of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel obtained in Example 1;

[0026] Figure 2 The fluorescence spectra of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel obtained in Example 1 at different excitation light wavelengths;

[0027] Figure 3 The stress-strain curves of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogels obtained in Examples 1 to 6;

[0028] Figure 4 This is a scanning electron microscope image of the polyvinyl alcohol-polyethyleneimine composite high-intensity fluorescent hydrogel obtained in Examples 1 to 6. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0030] Example 1

[0031] Polyvinyl alcohol was added to deionized water, and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0032] like Figure 1 and Figure 2 As shown, the maximum excitation wavelength of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel is 375nm, the maximum emission wavelength is 456nm, and the emission wavelength does not change with the change of the excitation wavelength, indicating that it is blue luminescence and has no excitation wavelength dependence like most intrinsic luminophores.

[0033] Example 2

[0034] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 5wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0035] Example 3

[0036] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 2wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0037] Example 4

[0038] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 8wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0039] Example 5

[0040] Polyvinyl alcohol was added to deionized water, and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 8wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 5wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0041] Example 6

[0042] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 8wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 2wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0043] like Figure 3 As shown in the figure, the mechanical properties of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel change significantly with the change of the feed concentration of polyvinyl alcohol, polyethyleneimine and citric acid. When the concentration of any feed decreases, the tensile strength decreases significantly.

[0044] like Figure 4 As shown in the figure, the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel has a uniform network structure and shows obvious regularity. As the feed concentration increases, the pore size of the double network hydrogel becomes more uniform and dense. The decrease in the pore size of the hydrogel is caused by the increase in the content of the polyethyleneimine network and the chain entanglement and molecular interaction between the double networks. The solid content of the hydrogel increases and the number of cross-linking sites increases, so the pore structure is denser. Similarly, when the content of the polyethyleneimine network is consistent, the increase in the content of the polyethyleneimine network also makes the hydrogel denser.

[0045] Example 7

[0046] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 20wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 20wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0047] Example 8

[0048] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 20wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 1wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0049] Example 9

[0050] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 2wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 20wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0051] Example 10

[0052] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 2wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 1wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0053] Embodiment 11

[0054] Polyvinyl alcohol was added to deionized water and stirred in a 90°C oil bath for 2 hours until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0055] Example 12

[0056] Polyvinyl alcohol was added to deionized water, and stirred in an oil bath at 100°C for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0057] Embodiment 13

[0058] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 120°C for 5 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0059] Embodiment 14

[0060] Polyvinyl alcohol was added to deionized water, and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 80°C for 100 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0061] Embodiment 15

[0062] Polyvinyl alcohol was added to deionized water, and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -25°C for 1 hour, then allowed to stand at 0°C for 4 hours, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0063] Example 16

[0064] Polyvinyl alcohol was added to deionized water and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at 0°C for 24 hours, then allowed to stand at 35°C for 1 hour, and freeze-thaw cycles were repeated 3 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0065] Embodiment 17

[0066] Polyvinyl alcohol was added to deionized water, and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and frozen and thawed once to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0067] Embodiment 18

[0068] Polyvinyl alcohol was added to deionized water, and stirred in a 95°C oil bath for 1 hour until clear to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 10wt.%, and then citric acid and polyethyleneimine were added to the polyvinyl alcohol aqueous solution to obtain a mixed solution, wherein the mass ratio of citric acid to polyethyleneimine was 1:2, and the total mass of citric acid and polyethyleneimine accounted for 10wt.% of the total mass of the mixed solution. The mixed solution was transferred to a three-necked flask, and heated and stirred at 100°C for 72 hours to complete the amidation reaction between polyethyleneimine and citric acid to form a polyethyleneimine network, and then subjected to freeze-thaw cycle treatment: frozen at -20°C for 18 hours, then allowed to stand at 25°C for 4 hours, and freeze-thaw cycles were repeated 5 times to form a polyvinyl alcohol network, and finally a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel was obtained.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel, characterized in that: It consists of a first network formed by cross-linking polyethyleneimine and citric acid and a second network formed by freeze-thaw cycles of polyvinyl alcohol.

2. The polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel according to claim 1, characterized in that: The mass ratio of citric acid to polyethyleneimine is 1:(0.5-5), and the ratio of the total mass of polyethyleneimine and citric acid to the mass of polyvinyl alcohol is 1:(0.2-19.8).

3. A method for preparing the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel according to claim 1 or 2, characterized in that: The following steps are involved: Citric acid and polyethyleneimine are added to a polyvinyl alcohol aqueous solution to obtain a mixed solution, and the mixed solution is subjected to a heating reaction and a freeze-thaw cycle to obtain a polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel.

4. The preparation method according to claim 3, characterized in that: The mass density of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 2 to 20 wt.%.

5. The preparation method according to claim 3, characterized in that: The total mass concentration of polyethyleneimine and citric acid in the mixed solution is 1-20wt.%.

6. The preparation method according to claim 3, characterized in that: The heating reaction temperature is 80°C to 120°C, and the time is 5 to 100 hours.

7. The preparation method according to claim 3, characterized in that: The freeze-thaw cycle is specifically placed in an environment of -25°C to 0°C for 1 to 24 hours and then placed in an environment of 0°C to 35°C for 1 to 4 hours, and repeated 1 to 5 times.

8. The preparation method according to claim 3, characterized in that: The polyvinyl alcohol aqueous solution is obtained by heating polyvinyl alcohol in water and dissolving it.

9. The preparation method according to claim 8, characterized in that: The temperature for heating and dissolving is 90℃~100℃, and the time is 1~2h.

10. Use of the polyvinyl alcohol-polyethyleneimine composite fluorescent hydrogel as claimed in claim 1 or 2 in the field of anti-counterfeiting.

Citation Information

Patent Citations

  • Branched polyethyleneimine based synthetic hybrid nano hydrogel and preparation and application thereof

    CN110368359A

  • Preparation method of polyethyleneimine-polyvinyl alcohol hydrogel with self-healing performance

    CN110698697A

  • Crosslinked hydrogels

    US20100272672A1